A Lightweight Approach to Academic Research Group Management Using Online Tools: Spend More Time on Research and Less on Management - Eaton, Eric (Proceedings of the AAAI Conference on Artificial Intelligence, 2019)
After years of taking a trial-and-error approach to managing a moderate-size academic research group, I settled on using a set of online tools and protocols that seem effective, require relatively little effort to use and maintain, and are inexpensive. This paper discusses this approach to communication, project management, document and code management, and logistics. It is my hope that other researchers, especially new faculty and research scientists, might find this set of tools and protocols useful when determining how to manage their own research group. This paper is targeted toward research groups based in mathematics and engineering, although faculty in other disciplines may find inspiration in some of these ideas.